Implementasi Audit Penjualan Dan Penagihan Oleh KAP Terhadap Perusahaan - Ningsih, Kartika Yulia; Amyar, Firdaus; Hernusa, Hardini Lestiani (Jurnal Aplikasi Bisnis Kesatuan, 2024)
The company's financial statements are a source of information for interested parties to find out the condition of the company. Audits are conducted to strengthen the trust of users of financial information. This final project presents information regarding the audit conducted by KAP Crowe's auditors on PT XYZ's financial statements, particularly on sales and billing accounts as accounts that experienced significant changes. Data collection was carried out using interview and observation methods as well as literature study which were then described in the discussion which included objectives, procedures, audit effects, and results of audits carried out on PT XYZ. The audit report shows that PT XYZ's financial statements are presented fairly without any exceptions.   Keywords: audit, procedures, sales, income statement